2001
DOI: 10.1177/03635465010290021101
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Calcaneoplasty

Abstract: Endoscopic calcaneoplasty offers access to the retrocalcaneal space, thereby making it possible to remove inflamed retrocalcaneal bursa as well as the posterosuperior part of the calcaneus in applicable cases of painful hindfoot. In this study, endoscopic calcaneoplasty was performed in 21 procedures in 20 patients. All of the patients had typical complaints of inflammation of the retrocalcaneal bursa that were unresponsive to nonoperative treatment for more than 6 months. In all patients a superior calcaneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
105
0
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(112 citation statements)
references
References 25 publications
3
105
0
4
Order By: Relevance
“…This score was chosen for comparing the results with other references [37]. Thirty-four patients presented good and 41 patients excellent The three patients with the poor results showed an ossified area of the Achilles tendon insertion (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This score was chosen for comparing the results with other references [37]. Thirty-four patients presented good and 41 patients excellent The three patients with the poor results showed an ossified area of the Achilles tendon insertion (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Dissections from cadaveric studies suggested the medial column of the Achilles tendon, the plantaris tendon, and the sural nerve are at risk in open and in endoscopic surgery [23,46]. Endoscopic retrocalcaneal decompression seems to be a promising method, and success rates greater than 90% have been reported in some case series [14,31,43]. Results of endoscopic and open Haglund's resection were similar in one comparative nonrandomized prospective case series with a success rate of 80% [21].…”
Section: Introductionmentioning
confidence: 93%
“…This entity was first described by Patrick Haglund in 1928 [24,31,43]. It is characterized clinically by localized pain and swelling at the medial and lateral distal Achilles tendon border resulting from retrocalcaneal bursitis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations